Stigmatisasi Terhadap Keluarga Inti Dan Relasi Terdekat Dari Terpidana Korupsi (Studi Kasus Keluarga Inti dan Relasi Terdekat Andi Malaranggeng): Universitas Islam Riau - Munir, Abdul; Nandana, Gilar (Sisi Lain Realita, 2019)
Stigmatization is a proces that give some certain individual an atribute that will lower their social status. At firts, stigma is an unformal punishement for someone who did an „evil‟ thing while that judgemen come from the society it self. Unfortunalety, stigma will became something reallly bad or even evilish because the difficulty for some one whoe get the stigma to get rid of it. This study focused on the form of stigma itself that affect not only the one who did bad or evil thing but their family and relatives as well. This study is descriptive study that have been selected purposely. The key dactor of study depends on the form of stigma that affect the family anda relatives of an individual who did that bada or evil thing.The result shown that some of stigmatization in the very miinimum level. Hopefully, the result of this studycan be use and help further study with similar topic.